Qu\~ao distante é longe? A importância da distância geográfica para fluxos de conhecimento - Patricia Alessandra Morita Sakowski (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper examines the importance of geographic distance for the occurrence of knowledge flows between countries and how this importance has been changing over time. The main channels for knowledge flows are presented and an econometric analysis conducted with a focus on knowledge flows generated by co-patenting activities. A gravity model is estimated using longitudinal count data for 97 countries covering the years 1977 to 2000. The results show that the importance of geographic distance for the co-invention of patents has been decreasing in time, but that this has been happening only in Europe and America and in high income countries. These findings suggest that although advances in communications technologies and lower transportation costs could potentially favor knowledge flows to developing countries and thus income convergence, they seem on the other hand to be helping already developed regions become more integrated whilst making peripheral ones lag relatively farther behind.
Keywords: O33; R12; R15; C23; 330; knowledge flows; geographic distance; gravity model; co-patenting; panel count data